Carbon stocks and soil sequestration rates of tropical riverine wetlands - Adame, M.F.; Santini, N.S.; Tovilla, C.; Vázquez Lule, A.; Castro, L.; Guevara, M. (Copernicus GmbH, 2015)
Abstract. Riverine wetlands are created and transformed by geomorphological processes that determine their vegetation composition, primary production and soil accretion, all of which are likely to influence C stocks. Here, we compared ecosystem C stocks (trees, soil and downed wood) and soil N stocks of different types of riverine wetlands (marsh, peat swamp forest and mangroves) whose distribution spans from an environment dominated by river forces to an estuarine environment dominated by coastal processes. We also estimated soil C sequestration rates of mangroves on the basis of soil C accumulation. We predicted that C stocks in mangroves and peat swamps would be larger than marshes, and that C, N stocks and C sequestration rates would be larger in the upper compared to the lower estuary. Mean C stocks in mangroves and peat swamps (784.5 ± 73.5 and 722.2 ± 63.6 MgC ha−1, respectively) were higher than those of marshes (336.5 ± 38.3 MgC ha−1). Soil C and N stocks of mangroves were highest in the upper estuary and decreased towards the lower estuary. C stock variability within mangroves was much lower in the upper estuary (range 744–912 MgC ha−1) compared to the intermediate and lower estuary (range 537–1115 MgC ha−1) probably as a result of a highly dynamic coastline. Soil C sequestration values were 1.3 ± 0.2 MgC ha−1 yr−1 and were similar across sites. Estimations of C stocks within large areas need to include spatial variability related to vegetation composition and geomorphological setting to accurately reflect variability within riverine wetlands.